Utilization of glycerol as substrate in the production of biosurfactant (Research, Society and Development, 2022)
Surfactants have surface active properties and micelle formation, they are molecular compounds with hydrophobic and hydrophilic portions, acting to reduce surface/interfacial tensions. In this context, glycerol, which is a waste generated in large quantities due to the increasing production of biodiesel worldwide, can be used as a substrate in the production of biosurfactants. Therefore, this work had as scope to perform a literature review on the use of glycerol, co-product of biodiesel synthesis, as substrate in the production of biosurfactants from Bacillus subtilis. The present research gathered from the qualitative analysis of bibliographic data related to the production of biosurfactants, factors that influence it, especially, of application in the environmental area. From the evaluation of published works in the area of interest, the bibliographic survey showed that glycerol is a promising carbon source in the production of biosurfactant, standing out when compared to other alternative sources. As well, the surfactant synthesized by B. subtilis, showed similarity with commercial surfactin, and potential in environmental bioremediation process, such as soil and water contaminated by hydrocarbons, heavy metals and oily compounds.